Gap Analysis of Providing Primary Health Care in Comprehensive Rural Health Centers of Iran - Fereshteh Fani; Ghahraman Mahmoudi; Mohammad Ali Jahani; Jamshid Yazdani-Charati (ACHSM, 2023)
Background: The lack of primary health care (PHC) assessment will lead to the lack of knowledge of the final client's needs and to deviation from the mission of the health system. This study was conducted to compare the understanding and experience of PHC providers and recipients regarding the principles of PHC in Iran. Methods: This cross-sectional descriptive-analytical study was conducted on Comprehensive Rural Health Centers (CRHCs) in 2022. The research population consisted of health service providers and recipients in rural areas. A Primary Care Assessment Tool (PCAT) was used. 410 child/ adolescent and 402 adult PCAT were completed by stratified cluster sampling method and 413 service providers were randomly selected. This questionnaire had 6 core domains and 3 ancillary domains. After collection and entering the Excel; data were analyzed by inferential statistics tests including Independent T-test and one-way ANOVA, by SPSS26 and STATA16 at the significant level of P>0.05. Results: Except for the Cultural Competence and Services Available domains, in the rest of the domains, there was not the same understanding between the service provider and recipient regarding PHC services. Also. child/adolescent PHC recipients had the same understanding as adult PHC recipients in the domains of Cultural Competence, Family Centeredness, Information System, Ongoing Care, and Access. But a significant difference was between the two groups in other domains, Primary Care Score, and Primary Care Expanded scores (P >0.05). Conclusions: For the common understanding between all three compared groups, cultural competence was the strongest component, and coordination-referral system, services provided, and community orientation were the weakest components. To fill this gap, increasing the health literacy of service recipients, real needs assessment, and providing services based on the needs of the community, reforming the processes of the referral system, and the commitment of the government to implement the processes seem necessary.